Persistence and cardiovascular outcomes with ramipril, atorvastatin, ASA as a single pill compared to the multi pill combination. A subanalysis of the START study, a claims data analysis. (25th November 2020) - Predel, H.G; Weisser, B; Wassmann, S; Schmieder, R.E; Blettenberg, J; Gillessen, A; Fournier, V; Noetel, A; Randerath, O; Boehm, M
Abstract: Background/Introduction: Large randomized clinical trials have shown the efficacy of aspirin (ASA), angiotensin converting enzyme inhibitors (ACEI) and statins (S) in secondary prevention. However, adherence to medication is low in patients suffering from a cardiovascular event and decreases with each additional tablet. Therefore, a single pill (SP) approach is considered to increase drug persistence and decrease cardiovascular events in this patient population. Purpose: Data that show an advantage for a SP regimen containing ASA, ACEI, and S compared to the identical loose combination (LC) regarding persistence, and clinical outcomes under conditions of daily practise in one study are missing. We conducted the START study to answer these questions. A subset, in which we anlysed data from patients in secondary prevention is presented here. Methods: The START study was a retrospective, non-interventional analysis of an anonymised claims dataset covering patients suffering from cardiovascular diseases insured by the German AOK PLUS public health insurance in the years 2012–2017. Patients at age ≥18 years with an indication for the use of a combination treatment in cardiovascular disorders – including the use of ASA, ramipril, and atorvastatin - in a SP or identical LC were followed up to 1 year. After 1:1-Propensity Score Matching (PSM) persistence (defined as redemption of prescription with a lack >60 days) and clinical outcomes were compared using non-parametric tests. Results: Before PSM, 564, 941 patients had a cardiovascular event in the medical history, 427, 046 suffered from coronary artery disease. 275 received the three substances described above as SP, 6, 662 as LC. After PSM, data from 211 patients were suitable for further analysis in each group. Baseline characteristics were comparable between SP and LC groups. Persistence to treatment was significant lower in the LC group (Hazard Ratio, HR, 0.25 [95% CI 0.19–0.34], p<0.001). 8 clinical outcomes were analysed. Lower Incidence Rate Ratio (IRR) was found in the SP group for myocardial infarction (IRR 0.46; 95% CI 0.07–2.36), stroke (IRR 0.51; 95% CI 0.04–4.46), transitory ischemic attac (IRR 0.77; 95% CI 0.01–60.12), coronary artery disease (IRR 0.60; 95% CI 0.25–1.43), and all cause mortality (IRR 0.38; 95% CI 0.06–1.79). All cause hospitalisation was significant lower in the SP group (IRR 0.58; 95% CI 0.47–0.72; p<0.001). Conclusion: The number of patients receiving a SP regimen in secondary prevention was relatively low. However, persistence to medication was significantly higher in the SP group. In addition, a tendency for a lower IRR was also observed for cardiovascular events and all cause mortality in the SP group. The results of our analysis support the use of a SP regimen in secondary prevention of cardiovascular events. Funding Acknowledgement: Type of funding source: None